Optimalisasi Program Pengabdian Masyarakat dalam Pemberdayaan Masjid Darul Muttaqin Desa Tanjung Terdana - Stiven Juliano Wiratama; Nurrahmat Hidayatul Ikhsan; Axsan Novemdi; Aliya Sunata; Elpa Cincu; Putri Julia; Desvita Sartini; Kurnia Oktamah Putri; Amanda Novry Oktavia Ningrum; Dika Ayu Safitri; Ektiva Utami (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
Community Service Program is a mandatory activity for all students at UIN Fatmawati Sukarno Bengkulu to apply the knowledge gained during their studies. It serves as a manifestation of their commitment to the community and is a prerequisite for advancing to the next stage of their education. In this context, students play a crucial role as agents of change. Through the Community Services Program, students can assist the community by providing training, counseling, mentoring, and helping to raise awareness about the potential within the village, as well as supporting the community in improving their quality of life in the future. The methodology used in this research is interviews, documentation, and observation. Based on the observations made, several issues can be concluded: (1) A lack of community awareness regarding revitalizing the mosque such as pray at the mosque due to exhaustion from working all day, (2) Inadequate facilities for local children to learn to read the Quran, and (3) The insufficient role of parents in educating their children, leading to local children being easily influenced by inappropriate language and behavior. Considering the issues at hand, several proposed work programs have been developed to address various challenges in the village.